Acute systemic exposure to silver-based nanoparticles induces hepatotoxicity and NLRP3-dependent inflammation. Issue 8 (13th September 2016) - Ramadi, Khalil B.; Mohamed, Yassir A.; Al-Sbiei, Ashraf; Almarzooqi, Saeeda; Bashir, Ghada; Al Dhanhani, Aisha; Sarawathiamma, Dhanya; Qadri, Shahnaz; Yasin, Javed; Nemmar, Abderrahim; Fernandez-Cabezudo, Maria J.; Haik, Yousef; et al.
Abstract: Nanoparticles (NPs) are increasingly being commercialized for use in biomedicine. NP toxicity following acute or chronic exposure has been described, but mechanistic insight into this process remains incomplete. Recent evidence from in vitro studies suggested a role for NLRP3 in NP cytotoxicity. In this study, we investigated the effect of systemic administration of composite inorganic NP, consisting of Ag:Cu:B (dose range 1–20 mg/kg), on the early acute (4–24 h post-exposure) and late phase response (96 h post-exposure) in normal and NLRP3-deficient mice. Our findings indicate that systemic exposure (≥2 mg/kg) was associated with acute liver injury due to preferential accumulation of NP in this organ and resulted in elevated AST, ALT and LDH levels. Moreover, within 24 h of NP administration, there was a dose-dependent increase in intraperitoneal neutrophil recruitment and upregulation in gene expression of several proinflammatory mediators, including TNF-α, IL-1β and S100A9. Histological analysis of liver tissue revealed evidence of dose-dependent hepatocyte necrosis, increase in sinusoidal Kupffer cells, lobular granulomas and foci of abscess formation which were most pronounced at 24 h following NP administration. NP deposition in the liver led to a significant upregulation in gene expression of S100A9, an endogenous danger signal recognition molecule of phagocytes, IL-1β and IL-6. The extent of proinflammatory cytokine activation and hepatotoxicity was significantly attenuated in mice deficient in the NLRP3 inflammasome, demonstrating the critical role of this innate immune system recognition receptor in the response to NP.